Homework Practices in Teaching of Serbian Language in Junior Grades of Primary Education - Stakić, Mirjana M.; Stamatović, Jelena D.; Maksimović, Jasna M. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
Various advantages and disadvantages of homework are discussed in the literature. The aim of this paper is to determine the advantages and disadvantages of homework practices in Serbian Language taught in junior grades of primary education. Implementation practices were examined from the standpoint of teachers with the aim of determining: the dynamics in assigning and reviewing homework, assessment methods and ways of communicating feedback, representation of different types of homework, and the evaluation of their contribution. The study was conducted in 2020 and 2021 on a sample of 123 teachers. The obtained results indicate that the homework practices in Serbian Language classes are characterized by the frequency and diversity of homework assignments, individualized approach, reviewing regularity, and positive perception of their contribution. However, the results also raise several important questions – excessive students workload; functionality of assessing homework as a learning tool; homework assessments; encouraging cooperative homework and communication related to it – and indicate the need for further research.